ARTEMISININ CONTENT ON ARTEMISIA ANNUA L. TREATED BY GLORIOSA SUPERBA SEEDS' WATER EXTRACT - R, Sri Indah; Susilowati, Ari; Widyastuti, Yuli; Yunus, Ahmad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to determine the artemisinin content on Artemisia annua L. treated by water extract of Gloriosa superba seeds. Methods: G. superba seeds obtained naturally on Krakal Beach, Gunung Kidul, and extraction used a maceration method by water solvent (1:1). A. annua L. sprouts were obtained from B2P2TOOT Tawangmangu. Treatment variables done on sprouts using various water extract concentration of G. superba seeds and soaking time on A. annua L. sprouts. Determination of artemisinin content in leaf extract of A. annua L. was done using KLT-densitometric method with n-hexane:ethyl acetate (4:1) as mobile phase. Result: The result showed that artemisinin content in plant treatment of G. superba seed water extract was higher (9.78 μg/μl [±3.21]–16.60 μg/μl [±1.39]) compared to control plants (6.39 μg/μl [±1.40]). The concentration water extract of G. superba seed affected the level of artemisinin in the treatment plant. On the other hand, the soaking of A. annua L. sprouts using the water extract of G. superba seed did not affect the level of artemisinin content. Conclusion: Artemisinin content in treatment plant by G. superba seed water extract treatment was higher compared to control plants.